Technology for educational equity: an analysis from and towards an intercultural pedagogy - Priegue Caamaño, Diana (Profesorado, Revista de Currículum y Formación del Profesorado, 2011)
The numerous changes that have been made in the context of an increasingly multicultural and interconnected society such as the present one, have been the source of greater concern regarding the acquisition of those skills that teachers may need throughout their career, focusing on skills related to the effective management of those classrooms with significant ethnic and cultural diversity. That is why, this paper is aimed at analyzing the potential profitability of technological devices in the process of teacher education, emphasizing their potential for creating new spaces of interaction, which, besides enhancing the development of intercultural competences, would allow supporting an education more committed to ensuring equity in the public sphere. Among the conclusions drawn from this study, we should highlight two closely related issues: on the one hand, the importance of implementing new methodological approaches in the initial training of future teachers; and, on the other hand, the need to make progress in the search for new formulas and strategies for continuous professional development which, since the establishment of online cooperative working structures, could promote a stronger connection between schools and teachers.